How knowledge workers gather information from the Web: Implications for peer-to-peer file sharing tools - Hyams, Jennifer; Sellen, Abigail (Hewlett-Packard Labs Technical Report, 2003)
The success of peer-to-peer (p2p) music-sharing has no doubt contributed to assumptions that individuals’ PCs are a vast untapped resource of assets just waiting to be unlocked. This includes the push for opening up our file spaces at work to allow peers access to previously inaccessible information. We explore the potential of these ideas and test some of the assumptions underlying them by looking at 16 knowledge workers’ file spaces in the context of Web information-gathering tasks. Knowledge workers’ file spaces are more like “workbenches” than “archives” and the information held within them is fundamentally different to that which is placed in shared information spaces. Work is carried out on information to make it shareable, yet this information is found side-by-side on the “workbench” with unshareable information. This leads us to question the potential value of enabling people to open up their file spaces without considering the reusability of this information for others.